INTEGRASI NAVIGASI DAN RASI BINTANG (Tradisi Astronomi Masyarakat Etnis Sulawesi): Indonesia - Hikmatul Adhiyah; Nur Aisyah (UIN ALAUDDIN MAKASSAR, 2024)
The existence of traditional knowledge about direction based on the position of the constellation is an intellectual work in the form of cultural manifestation, which was born as a form of identity of an ethnic group in Sulawesi. This knowledge is owned, applied, and maintained to this day by ethnic communities in Sulawesi. This is because there is an essence and existence of astronomy and ethnoastronomy as a science that continues to develop to this day. Based on this, the main problem in this study is how to determine navigation based on the constellations of the Sulawesi ethnic community in astronomy and ethnoastronomy. This study aims to determine and analyze the relationship between navigation and constellations of the Sulawesi ethnic community with astronomy and ethnoastronomy. Therefore, a qualitative descriptive method is used by describing the existing data sources, then analyzed inductively through an astronomical and ethnoastronomic approach. The results of the study show that the four ethnic communities of Sulawesi including the Bugis, Makasaar, Mandar, and Toraja ethnic groups have traditional knowledge about constellations to determine navigation in astronomical and ethnoastronomic observations.